2011
DOI: 10.1038/ncomms1610
|View full text |Cite
|
Sign up to set email alerts
|

River-margin habitat of Ardipithecus ramidus at Aramis, Ethiopia 4.4 million years ago

Abstract: The nature and type of landscape that hominins (early humans) frequented has been of considerable interest. The recent works on Ardipithecus ramidus, a 4.4 million years old hominin found at middle Awash, Ethiopia, provided critical information about the early part of human evolution. However, habitat characterization of this basal hominin has been highly contested. Here we present new sedimentological and stable isotopic (carbon and oxygen) data from Aramis, where the in situ, partial skeleton of Ar. ramidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 25 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Within this succession, the Ar. ramidus-bearing rock unit comprises silt and clay beds deposited on a floodplain," an interpretation also preferred independently by Gani and Gani (2011), who also found strong evidence of fluvial sedimentation and suggested the presence of riparian environments. This agrees with Cerling et al (2010), who suggested "a riparian corridor bordered by mixed and more open environments, including woody grasslands with !…”
mentioning
confidence: 70%
“…Within this succession, the Ar. ramidus-bearing rock unit comprises silt and clay beds deposited on a floodplain," an interpretation also preferred independently by Gani and Gani (2011), who also found strong evidence of fluvial sedimentation and suggested the presence of riparian environments. This agrees with Cerling et al (2010), who suggested "a riparian corridor bordered by mixed and more open environments, including woody grasslands with !…”
mentioning
confidence: 70%
“…Since the lice life cycle does not include a free‐living phase, the inferred Pthirus host species transfer would imply spatiotemporal overlap and physical contact between hominins and ancestral gorillas, probably between 4 and 3 MYA. A dearth of fossils makes it impossible to confidently reconstruct Pliocene gorilla habitats, and reconstructions of hominin paleoenvironments have been controversial . Nevertheless, given the absence of hominin and gorilla fossil co‐occurrence at sites in eastern or southern Africa and the tropical forest habitats of modern gorillas, the Pthirus lice speciation pattern suggests that our hominin ancestors may have inhabited a more diverse range of environments than typically is assumed.…”
Section: Hominin Evolutionmentioning
confidence: 99%
“…A dearth of fossils makes it impossible to confidently reconstruct Pliocene gorilla habitats, and reconstructions of hominin paleoenvironments have been controversial. [34][35][36] Nevertheless, given the absence of hominin and gorilla fossil co-occurrence at sites in eastern or southern Africa and the tropical forest habitats of modern gorillas, the Pthirus lice speciation pattern suggests that our hominin ancestors may have inhabited a more diverse range of environments than typically is assumed.…”
Section: Lice Loss Of Body Hair Archaic Hominin Contact and Clothingmentioning
confidence: 99%
“…Some specimens found above the DABT are overlain by the Wodara Basaltic Tuff (WOBT) ). WOBT, which is not dated, lies underneath the 4.317 6 0.055 Ma Kullunta Basaltic Tuff (KUBT), and Gani and Gani (2011) argue that an average sedimentation rate of 0.5 mm yr 21 between DABT and KUBT indicates that WOBT was likely deposited within 5 ky of the deposition of the DABT. Until an age for WOBT is determined, we use 4.262 Ma for the minimum LAD of Ar.…”
Section: Ardipithecus Ramidusmentioning
confidence: 99%